Regional co-ordinator for haemophilia in domiciliary practice. Issue 6090 (24th September 1977) - Colvin, B T; Aston, C; Davis, G; Jenkins, G C; Dormandy, K M
Abstract : The North-east Thames Region has appointed a nursing sister to co-ordinate the organisation of care for haemophiliacs in the region. As a result of the appointment, facilities for home treatment have expanded rapidly. Several associate centres providing care to haemophiliacs have been set up around the region in addition to the four main haemophilia centres, which are all in the south-west corner of the region. As well as providing support and supervision of patients on home treatment, the co-ordinator helps to place haemophiliac children in suitable schools, maintains the regional register of haemophiliacs, and has a more general role in ensuring that services are available where they are needed throughout the region.